Approach development to the expert committees formation for the assessment of teams of high-tech projects performers - Шостак, Олена Ігорівна (Technology audit and production reserves, 2016)
The object of research in this work – activities of innovative enterprises to implement high-tech projects (HTP). Subject of research – decision support tools on the formation of alternative teams of HTP performers as one of the key stages of forming teams of HTP performers at innovation enterprises is the selection of experts for collective assessment of applicants in the project team. The essence of the proposed approach is to create a sequence of stages for formation of the expert committee: the choice of a rational number of the expert committee members; generate a list of possible candidates for experts; creating preliminary list of the expert committee members and assessment of their competence; a final commission of experts indicating the competence of its members. Research results: methodology for determining the limit values (upper and lower) of expert committee size and assessment of the total number of experts in the committee; tool for determining the competence of individual members and expert committee as a whole, it is a special verbal-numeric scale and range of analytical expressions; four-phased approach to the formation of expert committees, which is a part of the management of high-tech projects for innovative enterprises. Use the proposed approach to the formation of expert committees for assessing the quality of teams of high-tech projects performers will enable enterprises to increase the efficiency of these projects by reducing the level of uncertainty about competence compliance and personal qualities of performers to complexity of the project.